2020
DOI: 10.1186/s12957-020-01832-9
|View full text |Cite
|
Sign up to set email alerts
|

Circ-FOXM1 contributes to cell proliferation, invasion, and glycolysis and represses apoptosis in melanoma by regulating miR-143-3p/FLOT2 axis

Abstract: Background: Numerous literatures have demonstrated that circular RNAs (circRNAs) are involved in multiple types of tumors. However, the effects of circRNAs in melanoma are not very clear. In this study, we aimed to investigate the roles and mechanisms of circ-FOXM1 in melanoma. Methods: Quantitative real-time polymerase chain reaction (qRT-PCR) was conducted to determine the expression of circ-FOXM1, microRNA-143-3p (miR-143-3p), and Flotillin 2 (FLOT2) mRNA. 3-(4,5-Dimethyl-2-thiazolyl)-2,5diphenyl-2-H-tetraz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Tian et al ( 2020 ) found that circ-FOXM1 promoted cancer progression in melanoma cells, which is consistent with findings in non-small-cell lung cancer (Liu G. et al, 2019 ). circ-FOXM1 manifests a sponging effect for miR-143-3p, a regulatory element of Flotillin 2 (FLOT2).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Tian et al ( 2020 ) found that circ-FOXM1 promoted cancer progression in melanoma cells, which is consistent with findings in non-small-cell lung cancer (Liu G. et al, 2019 ). circ-FOXM1 manifests a sponging effect for miR-143-3p, a regulatory element of Flotillin 2 (FLOT2).…”
Section: Resultssupporting
confidence: 77%
“…Red and blue color indicated the oncogenic and suppressive functions of circRNAs in different biological processes involved in melanoma progression, respectively. Up and down arrows indicated the activation and inhibition of physiological processes in melanoma pathogenesis, respectively (Bian et al, 2018 ; Ju et al, 2018 ; Luan et al, 2018 ; Wang Q. et al, 2018 ; Lin et al, 2019 ; Shang et al, 2019 ; Zou et al, 2019 ; Chen J. et al, 2020 ; Chen Z. et al, 2020 ; Hanniford et al, 2020 ; Jin et al, 2020 ; Lu and Li, 2020 ; Lu et al, 2020 ; Qian et al, 2020 ; Tian et al, 2020 ; Wei et al, 2020 ; Liu et al, 2021 ; Yin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been well defined that through their capability to simultaneously bind numerous miRNAs, circRNAs can act to sponge and inhibit the activity of various miRNAs [ 366 , 367 , 368 , 369 , 370 , 371 ], and similar to what is observed with many lncRNAs, this can result in profound alterations to the biological and metabolic processes important to tumorigenesis [ 368 ]. Studies have revealed that various circRNAs may act as oncogenic promoters in breast cancer [ 372 ], NSCLC [ 373 ], melanoma [ 374 ], gastric cancer [ 375 ], gallbladder cancer [ 376 ], and CRC [ 377 ] models. Furthermore, some of these studies have revealed that circRNAs may enhance carcinogenesis through impacting glycolysis and PKM2 expression levels ( Table 5 ).…”
Section: Emerging Areas Of Research Involving Pkm2mentioning
confidence: 99%
“…These effects were mediated through the regulation of miR-143-3p. Although the link between miR-143-3p and PKM2 is yet to be determined, the overexpression of miR-143-3p abolished lactate production and glycolysis in A2058 and A375 melanoma cells [ 374 ]. Likewise, the expression level of circ-NRIP1 in gastric cancer tissue and cells was shown to be upregulated.…”
Section: Emerging Areas Of Research Involving Pkm2mentioning
confidence: 99%